EFFECTIVENESS OF INFORMATION SERVICES WITH A CONTEXTUAL TEACHING AND LEARNING APPROACH TO IMPROVE INDEPENDENCE IN LEARNING - Tumiyem Tumiyem; Azizah Yusra Amaliyah Harahap; Indah Syasmita; Dewi Purnama Sari; Ibnu Hajar Nasution; Latifah Annisa; Mori Dianto (Universitas Labuhanbatu, 2026)
Purpose – This study aims to analyze the effectiveness of information services using the Contextual Teaching and Learning (CTL) approach in improving students' learning independence. The background of this study is the continued dominance of the lecture method in information services, which does not encourage student activity and independence. Therefore, a more contextual and participatory approach is needed.Methodology– This study uses a quasi-experimental framework featuring a non-equivalent control group pretest-posttest design. The research sample consisted of 56 students from grades XIA and XIB at SMK Negeri 1 Kutalimbaru, comprising 28 students in the experimental group and 28 in the control group. The instrument used was a Likert scale that had undergone Validation and reliability testing, with a significance value (Sig.) greater than 0.05. The research method involved a pretest, providing CTL-based information services to the experimental group, traditional services to the control group, and a posttest. The Wilcoxon test and t-test were used to analyze the data.Findings – The study found a difference in the increase in learning independence between the two groups. The experimental group obtained a higher average score (145.50) than the control group (137.21). The difference value after treatment was 8.29, indicating a moderate effect. This indicates that the CTL approach is more effective than conventional methods in increasing student learning independence.Contribution– This research provides practical guidance for guidance and counseling teachers on developing more innovative, interactive, and contextually relevant information services, enabling them to increase students' learning independence optimally